2009
DOI: 10.1097/qai.0b013e3181a24906
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Genetic Diversity and Transmitted Drug Resistance in Health Care Settings in Maputo, Mozambique

Abstract: The HIV-1 epidemic in Maputo is evolving rapidly in genetic complexity due to the recent introduction of all major subtypes and recombinant forms. Continued surveillance of drug resistance in treated and untreated populations is needed to prevent further transmission of HIV drug-resistant variants and maximize the efficacy of antiretroviral therapy in Maputo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…This is in accordance with previous studies showing that subtype C is the most frequent in Mozambique 14,15 and is consistent with previous studies showing the existence of this subtype in neighboring countries such as South Africa, with the exception to Tanzania where subtype A1 predominates. 16,17 Similarly, in Mozambique subtype G has previously been found in drug-naive patients enrolled from 2002 to 2004 and subtype A1 was recently introduced from patients enrolled in 2010.…”
Section: Aids Research and Human Retrovirusessupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with previous studies showing that subtype C is the most frequent in Mozambique 14,15 and is consistent with previous studies showing the existence of this subtype in neighboring countries such as South Africa, with the exception to Tanzania where subtype A1 predominates. 16,17 Similarly, in Mozambique subtype G has previously been found in drug-naive patients enrolled from 2002 to 2004 and subtype A1 was recently introduced from patients enrolled in 2010.…”
Section: Aids Research and Human Retrovirusessupporting
confidence: 82%
“…16,17 Similarly, in Mozambique subtype G has previously been found in drug-naive patients enrolled from 2002 to 2004 and subtype A1 was recently introduced from patients enrolled in 2010. 15,18 Furthermore, recombinant analysis using the jpHMM program showed that one (Sequence ID A037) of the sequences was a mosaic form composed of subtypes C/A1. The C/A1 mosaic form identified in this study could represent a new CRF or URF, but full genomic analysis and further studies in other regions of Mozambique are required to confirm this finding.…”
Section: Aids Research and Human Retrovirusesmentioning
confidence: 99%
“…84 Phylogenetic analyses have been employed in TDR prevalence studies primarily to characterize the extensive genetic diversity in specific regions 9094 and the dominance of HIV-1C in southern Africa. 9599 Few studies have evaluated transmission lineages of drug resistant strains through transmission cluster analysis to support or refute epidemiological linkages.…”
Section: Phylogenetics and Transmission Dynamics In Generalized Epidementioning
confidence: 99%
“…The study participants harboring the M36I mutation did not show a particular predominance of any HIV-1 subtype (subtype A, n = 4; subtype B, n = 3; subtype CRF-02AG, n = 4; subtype CRF-02AD, n = 1). R41K, H69K, L89M, and I15V were reported to be more frequent in subtype C [25,36]. In this study, one patient was infected with HIV-1C harboring R41K, H69K, and I15V.…”
Section: Drug Resistance Mutations Among the Study Participantsmentioning
confidence: 93%
“…These samples were used to determine HIV-1 RNA viral load, which was determined via quantification of HIV-1 viral RNA using COBAS AMPLICOR HIV-1 MONITOR Test version 1.5 (Roche Molecular Diagnostics, Basel, Switzerland) [24,25].…”
Section: Clinical and Virologic Characteristicsmentioning
confidence: 99%